PELUANG PENGEMBANGAN AGROINDUSTRI BERBASIS PERIKANAN LAUT DI DUSUN PAYANGAN DESA SUMBEREJO KECAMATAN AMBULU KABUPATEN JEMBER - Syamsul Hadi; Nurul Fathiyah Fauzi (Bogor Agricultural University, 2016)
ABSTRACTThe development of agro-industries through the development of domestic industry based fisheries in the Payangan hamlet Sumberejo District of Ambulu Jember faced with various problems that started from the central issue is the level of knowledge and skills is relatively low, the ownership of venture capital is relatively limited, the production activities as individuals not groups, access difficult commercial lending and access to technology is also difficult. These conditions resulted in labor productivity and production quality is low. The purpose of this study were: 1) Knowing the agro-industry development opportunities based marine fisheries; 2) Analyze the added value of the fish catch if processed further; and 3) to analyze the socio-economic factors that affect the chances of developing agro-industries based marine fisheries. The method used is descriptive quantitative and qualitative survey techniques. Types of populations in this study were fishermen and craftsmen, artisans and fishermen of each sampl e taken as many as 10, 11 and 9 of the techniques of simple random sampling and quota sampling, while the data collection techniques used depth Interview. Analysis of the data used to answer the purpose of the first, second and third use analysis tools respective R / C Ratio, Value-added models Hayami and probability cumulative logit model. The results of this study concluded: 1) Opportunities-based agro-industrial development of marine fish in the study area is wide open (R / C = 4.61); 2) Activity based agro-industry marine fish that includes pemindangan, fogging and making shrimp paste provide added value as much as Rp 43,672.02 per kg per production process; and 3) Simultaneously five independent variables significantly affect the chances of developing agroindustry and the partial factor significant business experience, whereas other estimators factors had no significant effect.Keywords: added value, agro-industry, development opportunities ABSTRAK Pengembangan agroindustri melalui pengembangan industri rumah tangga yang berbasis perikanan di Dusun Payangan Desa Sumberejo Kecamatan Ambulu Kabupaten Jember dihadapkan pada berbagai masalah yang dimulai dari masalah pokok yaitu tingkat pengetahuan dan ketrrampilan relatif rendah, kepemilikan modal usaha relatif terbatas, kegiatan produksi secara perseorangan tidak berkelompok, akses pinjaman modal usaha sulit dan akses teknologi juga sulit. Kondisi ini mengakibatkan produktivitas tenaga kerja dan kualitas produksi menjadi rendah. Tujuan penelitian ini adalah: 1) Mengidentifikasi peluang pengembangan agroindustri berbasis perikanan laut; 2) Menganalisis nilai tambah hasil tangkapan dalam bentuk olahan; dan 3) Menganalisis faktor sosial ekonomi yang mempengaruhi peluang pengembangan agroindustri berbasis perikanan laut. Metode penelitian yang digunakan adalah deskriptif-kuantitatif dan kualitatif melalui teknik survei. Target responden adalah nelayan sekaligus pengrajin, pengrajin dan nelayan, sebanyak masing-masing 10, 11 dan 9 orang melalui teknik simple random sampling dan quota sampling. Teknik pengumpulan data digunakan depth Interview. Analisis data yang digunakan untuk menjawab tujuan pertama, kedua dan ketiga digunakan alat analisis masing-masing R/C Ratio, nilai tambah model Hayami dan probabilitas komulatif Model Logit. Adapun hasil penelitian ini menyimpulkan: 1) Peluang pengembangan agroindustri berbasis ikan laut di daerah penelitian sangat terbuka lebar (R/C = 4,61); 2) Kegiatan agroindustri berbasis ikan laut yang meliputi pemindangan, pengasapan dan pembuatan terasi memberikan nilai tambah sebanyak Rp43.672,02 per kg per proses produksi; dan 3) Secara simultan kelima variabel bebas berpengaruh nyata terhadap peluang pengembangan agroindustri dan secara parsial faktor pengalaman berusaha berpengaruh nyata, sedangkan faktor penduga lainnya tidak berpengaruh nyata.Kata kunci: nilai tambah, agroindustri, peluang pengembangan